Problems and Prospects of Anti-Theft and Mobile Phone Tracking: A case in Nigeria - Adam, Iliyasu Yahaya; Varol, Cihan; Varol, Asaf (Ieee, 2019)
The study addresses some security challenges and opportunities brought by mobile phone tracking technologies, especially in the business of selling and buying used handsets. Cases, for instant, arise on the issue of stolen or missing phones. Some of the cases may involve the police, who make digital investigations to apprehend the culprits. However, as a result of some complainants' inability to provide details that will aid the police in making successful investigation, an innocent person or persons may be mistakenly apprehended as the culprit of a phone-theft related crime. The paper reviews literature on Anti-Theft and mobile tracking technologies, with the aim of providing guidance and awareness for phone owners and the potential buyers/sellers of used mobile phones who want to protect their handsets against any other GSM related issues.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: Anti-theft; phone tracking; smartphone; android; digital investigation